Empowering the Intellectually Disabled: Innovations and Pathways to Employment Inclusion (Journal of Human Sciences, 2025)
This review paper explores the trajectory of employment inclusion and economic empowerment for intellectually disabled individuals, analyzing historical perspectives, current practices, and future directions in the field. Through a comprehensive examination of global policies, innovative practices, and emerging trends, the paper highlights ongoing challenges, such as stigma and limited access to opportunities, while also identifying promising innovations, including remote work arrangements, technology-driven solutions, and entrepreneurship initiatives. By synthesizing lessons learned from successful policy frameworks and identifying areas for future research and pilot programs, the paper underscores the importance of collective action and commitment to creating a more inclusive and equitable workforce for all individuals, regardless of ability